Inhaled Water and Salt Suppress Respiratory Droplet Generation and COVID-19 Incidence and Death on US Coastlines - Rachel D. Field; Nathan Moelis; Jonathan Salzman; Adriaan Bax; Dennis Ausiello; Sophie M. Woodward; Xiao Wu; Francesca Dominici; David A. Edwards (Molecular Frontiers Journal, 2021)
Dry air alters salt and water balance in the upper airways and increases the risks of COVID-19 among other respiratory diseases. We explored whether such upper airway variations in salt and water balance might alter respiratory droplet generation and potentially contribute to observed impacts of airway hydration on respiratory disease. In a randomized 4-arm study of 21 healthy human subjects we found that the breathing of humid air, the wearing of cotton masks, and the delivery of (sodium, calcium, and magnesium chloride) salt droplets sized to deposit in the nose, trachea, and main bronchi similarly reduce the exhalation of respiratory droplets by approximately 50% ([Formula: see text] < 0.05) within 10 minutes following hydration. Respiratory droplet generation returns to relatively high baseline levels within 60–90 minutes on return to dry air in all cases other than on exposure to divalent (calcium and magnesium) salts, where suppression continues for 4–5 hours. We also found via a preliminary ecological regression analysis of COVID-19 cases in the United States between January 2020 and March 2021 that exposure to elevated airborne salt on (Gulf and Pacific) US coastlines appears to suppress by approximately 25%–30% ([Formula: see text] < 0.05) COVID-19 incidence and deaths per capita relative to inland counties — accounting for ten potential confounding environmental, physiological, and behavioral variables including humidity. We conclude that the hydration of the upper airways by exposure to humidity, the wearing of masks, or the breathing of airborne salts that deposit in the upper airways diminish respiratory droplet generation and may reduce the risks of COVID-19 incidence and symptoms.